Incidence of HTLV-1-associated myelopathy in the UK from 1991 to 2024: a longitudinal observational cohort study - Rosadas, Carolina; Baylon, Jerico; Greiller, Claire; Adonis, Adine; Dhasmana, Divya; Davies, Nicholas W. S.; Taylor, Graham P. (Frontiers in Medicine, 2025)
IntroductionHuman T-cell lymphotropic virus type 1 (HTLV-1) may cause spinal cord inflammation, leading to HTLV-1-associated myelopathy (HAM). HAM is a chronic and progressive neurological disorder that is associated with increased mortality and impaired quality of life. There are limited data on the incidence of HAM, with higher rates seen in Latin America and the Caribbean compared to Japan. We investigated the incidence of HAM in a cohort of initially asymptomatic people with HTLV-1 in the United Kingdom (UK).MethodsThis is a longitudinal retrospective observational study of people with confirmed HTLV-1 infection who first attended the National Centre for Human Retrovirology in London, UK, between 1st March 1991 and 31st March 2024. Clinical records were analysed to calculate the incidence rate and cumulative incidence of HAM. A secondary analysis was conducted to assess HAM incidence in people living with HTLV-1 and HIV coinfection. At the first visit, the HTLV-1 proviral load was compared between incident cases and those who remained asymptomatic during follow-up.ResultsIn a cohort with up to 33 years of follow-up of individuals living with HTLV-1 in the UK, the cumulative incidence of HTLV-1-associated myelopathy (HAM) was found to be 1.35% (4/297), with an incidence rate of 1.98 per 1,000 person-years. All people who developed HAM had a high proviral load at the first clinic visit. No cases of incident HAM were observed among individuals who had HIV-HTLV-1 coinfection during the study period.DiscussionThe incidence of HAM in the UK cohort is comparable to the rates reported in Latin America and the Caribbean and is higher than reported in other high-income countries. High proviral load of HTLV-1 predates the development of HAM.